Effect of Initial Prednisone Dosing on Ocular Myasthenia Gravis Control. Issue 4 (December 2021) - Shah, Yesha S.; Henderson, Amanda D.; Carey, Andrew R.
Abstract : Background: Ocular myasthenia is an autoimmune condition that results in double vision or ptosis. It often requires treatment with prednisone for immunosuppression, but there have been no prospective trials to help clinicians determine ideal dosing. Methods: This was a retrospective study comparing myasthenia symptom control at 1 month between patients treated with a maximum daily equivalent dose of prednisone less than 20 mg (low-dose group) vs 20 mg or more (medium-dose group). Results: Thirty-nine patients were identified: 19 patients in the low-dose group with mean maximum daily dose of 10 mg and 20 patients in the medium-dose group with a mean maximum daily dose of 29 mg. The low-dose group had 75% controlled or significantly improved at 1 month, and the medium-dose group had 74% controlled or significantly improved at 1 month, P = 0.94. The overall seropositivity rate was 64%, with 84% of the antibody-positive group being controlled or significantly improved at 1 month and 57% of the antibody-negative group being controlled or significantly improved at 1 month, P = 0.07, and no difference in prednisone dosing between the 2 groups. Conclusion: Based on the results of this small retrospective study, it seems initial treatment for ocular myasthenia gravis with a mean maximum daily prednisone dose of 10 mg is similarly effective compared with mean maximum daily dose of 29 mg for control at 1 month.